Ethical and Psychological Challenges in Human-AI Romantic Relationships: An Interdisciplinary Critical Study - Zhou, Benhong; Guan, Shuwen (Innovative Applications of AI, 2025)
This study explores the ethical and psychological challenges posed by romantic relationships between humans and artificial intelligence (AI), particularly focusing on how the technological evolution of AI companions deconstructs traditional interpersonal paradigms through novel forms of intimacy. On the ontological level, the ethical identity of AI companions introduces a paradox of subjectivity, questioning whether an instrumental existence can bear emotional responsibility. From a psychodynamic perspective, the applicability of Bowlby's attachment theory in asymmetric relationships is debatable, while the phenomenon of cognitive dissonance exhibits bidirectional effects in user-AI interactions. Users engage in self-deception to avoid genuine emotions in parasocial relationships, whereas designers face ethical dilemmas in emotional engineering. Based on these insights, this paper proposes a hierarchical governance model based on relationship depth and innovative approaches to user cognitive education.